(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the coverage of the Food and Nutritional Surveillance System (SISVAN) for children under 2 years of age in Northeastern Brazil and to characterize their nutritional status and food consumption, according to sex and data source, in 2019. Methodology: This is a cross-sectional study, whose data collection was carried out through public reports of SISVAN. Association analyzes were performed using the chi-square test, considering values of p <0.05. Results: The general coverage was less than 50% for both Northeast region and Northeast states, except for Paraíba (54.07%), and food coverage was 5.50% for region. Regarding nutritional status, high excessive weight (20.64%), weight deficit (7.89%) and height deficit (18.1%) were observed, all statistically higher for males. About food consumption markers among children aged 6 to 23 months, the consumption of ultra-processed foods (46.84%), sweetened drinks (28.33%), instant noodles, packaged snacks or crackers (22.77%) and filled cookies, sweets or treats (25.6%) were considered high. The consumption of foods rich in iron was low (14.65%). Exclusive breastfeeding was observed in less than half of children under 6 months (44.58%), the introduction of food at 6-8 months was low (23%) and almost half of children between 6 and 23 months were not in continued breastfeeding (44%). Conclusion: The coverage of the SISVAN is incipient for Northeastern children under 2 years of age, who keep inappropriate eating practices, low breastfeeding, and high excessive weight, weight deficit and height deficit.